Rejestracja polskich zbiorów bibliotecznych - widziana z perspektywy polskich bibliotek (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
During World War II, the Polish state and Polish culture suffered enormous, in many cases difficult to estimate due to the lack, destruction or loss of documentation. This situation was caused mainly by the destructions resulting from hostilities, the accidental ones, but mostly deliberate and deliberately planned. In addition, there was a plunder of Polish cultural goods by the German and Soviet invaders, and then by the occupant. The balance of losses resulting from the destruction and theft, despite many attempts made, starting with Karol Estreicher, through immortalized in post-war reports, reports, sometimes also in publications, taken almost immediately after the end of the war and after a longer break, in the 1990s, they still remain an open tab. The aim of the text is to present the state of knowledge about the extent and scope of losses of larger Polish libraries in large and medium-sized towns, libraries of various provenance, public, scientific and pedagogical during World War II. Therefore, a survey addressed to selected Polish libraries was conducted in 2021. Specific objectives included finding out what the library had done so far to register and recover lost collections before and after 1989. Libraries were asked what had been recovered so far. The survey found whether libraries cooperate with foreign institutions, in particular with libraries, to determine where the lost works are stored. The subject of interest was also obtaining knowledge whether the library cooperates in the field of registration and recovery of war losses with institutions of the Polish state established for this purpose, in particular with the Ministry of Culture and National Heritage, the Ministry of Foreign Affairs and the Ministry of Justice. As a result, it was also possible to find out whether the library, on its own, undertook work aimed at registration and recovery of war losses. The survey results will be presented and discussed in detail. In addition, the state of work on the registration and recovery of war losses in the Silesian Library in Katowice is presented using the case study method. At the end, conclusions and research postulates were presented.